IFN-β differentially regulates the function of T cell subsets in MS and EAE. (August 2016) - Kavrochorianou, Nadia; Markogiannaki, Melina; Haralambous, Sylva
Highlights: T cell targeting therapies in MS act either directly or indirectly. Endogenous and exogenous IFN-β regulate pro- and anti-inflammatory responses. IFN-β differentially affects T cell subsets involved in MS and EAE. Homeostatic functions of IFN-β are disease staging and setting context-dependent. Abstract: Multiple sclerosis (MS) is considered as a T cell mediated autoimmune disease of the CNS, although a pathogenic role has also been attributed to other immune cell types as well as to environmental and genetic factors. Considering that T cells are interesting from an immunopathogenic point of view and consequently from a therapeutic perspective, various T cell targeted therapies have been approved for MS. Interferon beta (IFN-β) is widely used as first-line intervention for modulating T cell responses, although its pleiotropic and multifaceted activities influence its effectiveness on the disease development, with mechanisms that are not yet fully understood. Since different T cell populations, including pro-inflammatory and regulatory T cells, might affect the course of MS, the effects of IFN-β become even more complex. This review will summarize recent findings regarding the T cell targeted effect of IFN-β in MS and its animal model EAE, with emphasis on the direct actions of endogenous and exogenous IFN-β on each T cell subpopulation involved in CNS autoimmunity. Delineating how IFN-β exerts its action on different T cell types may eventually contribute to the designing of therapeutic strategies aiming to improve the effectiveness of this drug for MS treatment.